EVALUTION OF ANTIMICROBIAL ACTIVITY OF PARTIAL PURIFIED BACTERIOCIN FROM LOCAL ISOLATE OF BACILLUS LICHENIFORIMS HJ2020 MT192715.1 - & Auda, Jebur (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to produce bacteriocin from Bacillus. licheniformis isolated from local soil of corn and sunflower fields and using as antimicrobial agent . Fourteen of local isolates of Bacillus sp. were obtained and ability of these isolates for growth on Brain heart infusion agar (BHI) at 550C were tested. Isolate C4 was revealed high growth density in comparison with other isolates. Isolate C4 was identified as Bacillus licheniformis according to morphological, cultural and biochemical tests, Moreover genetic analysis for 16S rRNA gene and given accession number MT192715.1 in GenBank of NCBI . Production of bacteriocin from this isolate was carried out in Luria Broth (LB) and partially purified by precipitation with 30-70 % saturation of ammonium sulfate followed by concentrated using poly ethylene glycol (PEG).The antimicrobial activity of partially purified bacteriocin was assayed against many species of food spoilage microorganism. Results were revealed that anitimicrobial activity of bacteriocin were between (0 - 360 ) units / ml. Stability of antimicrobial activity of partially purified bacteriocin toward Staphylococcus aureus were tested after incubation at different values of pH, temperature and some of enzyme which included proteolytic enzymes, α-amylase and lipase .The results indicated that residual inhibition activity of bacteriocin were varied according to conditions of incubation and type of treatment .